Alien 3 [videorecording (DVD)] - Weaver, Sigourney, 1949-; Dutton, Charles S.; Dance, Charles; Henriksen, Lance, 1940- (Twentieth Century Fox Home Entertainment, 2006)
Lt. Ripley is the only survivor when her spaceship crash lands on Fiorina 161, an area inhabited by former inmates of the planet's prison. Ripley fears an Alien was aboard her ship and soon evidence begins to appear. Without modern technology, she must lead the inmates into battle with the horrible creature.